Challenges with communication of critical laboratory results in a resource-limited setting in South Africa - Ameerah Davids; Annalise E. Zemlin; Elsie C. Kruger (AOSIS, 2024)
Background: Critical laboratory results are test results suggesting a patient is in immediate danger unless treatment is administered promptly. There is a paucity of studies in sub-Saharan Africa on clinicians' utility of these results and affected patients' outcomes. In our resource-limited setting in South Africa, we rely on telephonic communication to convey critical results. Objective: The aim of this study was to determine the average time for clinicians to acknowledge these results on the laboratory information system and to determine the outcome of affected patients. Methods: A retrospective descriptive audit at Tygerberg Academic Hospital was conducted between 01 October 2021 and 31 March 2022. Critical results and the time of acknowledgement by clinicians on the laboratory information system were obtained from inpatients and outpatients. One hundred and twenty inpatient critical results were randomly selected for a folder review to determine patient outcome. Results: Overall, 2514 critical results were reported, and 63 results were excluded. The remaining 2451 results were obtained from 1346 patients. The majority (94.5%) of results were obtained from inpatients, where 1681 (68.6%) were acknowledged within 24 h. The folder audit of 120 patients determined that 40 (33.3%) patients demised. In 82 (68.3%) patients, communication of a critical result did not alter clinical management. Conclusion: Critical laboratory results are crucial to patient care. This study found that approximately one-third of critical laboratory results were not used within 24 h. Engaging clinicians in current practice and implementing a means of improved communication of critical results is required. What this study adds: The study adds to the evidence of challenges experienced with communicating critical results to clinicians which could impact patient care. This is especially true in resource-limited settings; clinicians need to be made aware of the importance of these results, and communication modes need to be improved.